1991
DOI: 10.1002/ajmg.1320400205
|View full text |Cite
|
Sign up to set email alerts
|

Osteodysplastic variant of primordial dwarfism

Abstract: A patient with intrauterine growth retardation and marked postnatal retardation of growth had microcephaly and the orofacial and dental characteristics of the Seckel phenotype. In addition she had short forearms, metaphyseal flare, especially of the distal femora, triangular distal femoral epiphyses, and pseudoepiphyses of the hands, all characteristics of an osteodysplastic variant. Parental consanguinity suggests autosomal recessive inheritance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
2

Year Published

1995
1995
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 12 publications
0
17
0
2
Order By: Relevance
“…These age-related phenomena are similar to those of Seckel syndrome [Poznanski et al, 1983]. The reported patients share many features with an MOPD patient who was reported to have long and slender clavicles, ivory epiphyses, cone-shaped epiphyses, dislocated hip, with abnormal dental development [Shebib et al, 1991]. The panoramic radiograph of that particular patient and ours showed similar features consisting of microdontia, rootless molars, and severely hypoplastic alveolar process [Shebib et al, 1991].…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…These age-related phenomena are similar to those of Seckel syndrome [Poznanski et al, 1983]. The reported patients share many features with an MOPD patient who was reported to have long and slender clavicles, ivory epiphyses, cone-shaped epiphyses, dislocated hip, with abnormal dental development [Shebib et al, 1991]. The panoramic radiograph of that particular patient and ours showed similar features consisting of microdontia, rootless molars, and severely hypoplastic alveolar process [Shebib et al, 1991].…”
Section: Discussionmentioning
confidence: 52%
“…The reported patients share many features with an MOPD patient who was reported to have long and slender clavicles, ivory epiphyses, cone-shaped epiphyses, dislocated hip, with abnormal dental development [Shebib et al, 1991]. The panoramic radiograph of that particular patient and ours showed similar features consisting of microdontia, rootless molars, and severely hypoplastic alveolar process [Shebib et al, 1991]. Disproportionate short stature, synostosis of sagittal suture, short neck, short and bowed forearms, flared distal metaphyses of the femora, hypoplastic pelvis, and delayed intellectual development distinguish that patient from the current patients.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Willems et al [1987] reported a family with consanguinity and suggested that there might be an autosomal recessive basis for the disorder and Verloes et al [1987] reported another consanguineous family with two affected siblings. Herman et al [1991] reported an additional female and Shebib et al [1991] reported a girl from a consanguineous Saudi Arabian family who had only 11 ribs and had very little response to growth hormone therapy.…”
Section: Historical Perspectivementioning
confidence: 98%
“…All together at least 26 reports of affected individuals have been published in the medical literature [Brizard et al, 1973;Anoussakis et al, 1974;Pasquino and Iannaccone, 1978;Boscherini et al, 1981;Tsuchiya et al, 1981;Majewski andGoecke, 1982, 1998;Majewski et al, 1982b;Poznanski et al, 1983;Toudic et al, 1983;Verloes et al, 1987;Willems et al, 1987;Herman et al, 1991;Shebib et al, 1991;Sugio et al, 1993;Théau and Maroteaux, 1993;Al Gazali et al, 1995;Masuno et al, 1995;Spranger et al, 1996;D'Angelo et al, 1998;Halder et al, 1998;Tekin et al, 2000;Fukuzawa et al, 2002;Kantaputra, 2002;Seymen et al, 2002;Nishimura et al, 2003], in which 27 affected individuals have sufficient clinical information on natural history to be included in this report. This report describes the natural history of MOPD II based on the 27 published cases and 31 additional unpublished affected individuals.…”
Section: Introductionmentioning
confidence: 97%